View from the Bastions, Vienna - Wallis, Robert, 1794-1878 (engraver):::Creator::::::::::::; Bartlett, William Henry, 1809-1854 (artist):::Contributor::::::::::::
Hand-colored engraving of Vienna viewed from the Bastions